The Implication of Politeness and Speech Styles in Code Switching of Youth Javanese - Riris Sugianto (Universitas Teknologi Mataram, 2019)
The objective of this study is to present the use of code switching as expressions of politeness in Javanese language. This article is concern on the domain of family, in the terms of discourse analysis. This article present how the youth generation can not acquire the formal styles of Javanese (basa), therefore they tend to do code-switching from formal styles of Javanese (basa) to the use of informal styles of Javanese (ngoko) or to our national language, Indonesian. It provides definitions of politeness by theorists and presents some of the problems related to the concepts of politeness and speech styles in code-switching In Javanese families specifically for the youth generation. Furthermore, it looks into the differences usage of speech styles for both the parents as the elders and children as the youngers in the families. There are some factors of youth Javanese to switch their code. The factors are the participants, the topic, the setting and the function. One important key is every language always has stable characteristics, but it could be dynamic especially when the language (Javanese) exists side by side with another language (Indonesian). Technically, in the communication, the modification of language usage such as code switching that made by the speaker will be occur and unavoidable.